Neuromuscular Performance and Hormonal Responses to Military Operational Stress in Men and Women. Issue 5 (May 2021) - Conkright, William R.; Beckner, Meaghan E.; Sinnott, Aaron M.; Eagle, Shawn R.; Martin, Brian J.; Lagoy, Alice D.; Proessl, Felix; Lovalekar, Mita; Doyle, Tim L.A.; Agostinelli, Phil; Sekel, Nicole M.; Flanagan, Shawn D.; et al.
Abstract : Abstract: Conkright, WR, Beckner, ME, Sinnott, AM, Eagle, SR, Martin, BJ, Lagoy, AD, Proessl, F, Lovalekar, M, Doyle, TLA, Agostinelli, P, Sekel, NM, Flanagan, SD, Germain, A, Connaboy, C, and Nindl, BC. Neuromuscular performance and hormonal responses to military operational stress in men and women. J Strength Cond Res 35(5): 1296–1305, 2021—Women have recently been integrated into ground close combat positions; however, there are limited data in women in these roles. We aimed to test the hypothesis that there would be no sex-specific neuromuscular responses, but hormonal signaling would be differentially impacted when exposed to simulated military operational stress (SMOS). Neuromuscular performance was assessed daily using a tactical mobility test (TMT) in 54 male and 15 female military members. Blood was drawn before/after TMT. Mood states were assessed each morning. Unloaded 300-m shuttle time increased 6% in both sexes and remained 7% higher after 1 day of recovery compared with baseline ( p < 0.05 for both), whereas performance was maintained in other TMT events ( p > 0.05). Growth hormone increased in men, but not women, before to after TMT ( p < 0.001 vs. p = 0.086). Women experienced a greater decline in insulin-like growth factor-I across days compared with men ((Equation is included in full-text article.) = 0.778 vs. 0.209, respectively, p < 0.001). Brain-derived neurotrophic factor increased significantly in men only from before to after TMT on day 1 (men: +107% vs. women: +10%) but no difference on days 3 or 4. Cortisol increased 69% from before to after TMT when averaged by sex and day. Negative mood states (depression, tension, and anger) and altered hormonal concentrations were associated with poorer TMT performance. Acute SMOS differentially impacted circulating hormonal milieu in men and women, but no differences in physical performance responses. Unloaded 300-m shuttle was negatively impacted while other fitness domains were maintained. Relationships between performance and mood/endocrine signaling highlight the potential for self-report measures and biomarkers to serve as indicators of performance change.